2019
DOI: 10.1111/1750-3841.14464
|View full text |Cite
|
Sign up to set email alerts
|

Ostwald Ripening Rate of Orange Oil Emulsions: Effects of Molecular Structure of Emulsifiers and Their Oil Composition

Abstract: Ostwald ripening, one of the frequently observed instability of flavor oil emulsions, can be easily prevented by adding triacylglycerols to the oil phase. The effect of interfacial characteristics of the emulsion droplets (particularly thickness) on the effectiveness of triacylglycerol inhibition of Ostwald ripening was evaluated in this study. The prepared emulsions were stabilized with emulsifiers with different‐size hydrophilic groups, which correlate to droplet interfacial thickness. Emulsions with an oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A different way to achieve small-sized nanoemulsions with higher long-term stability is to incorporate more hydrophobic molecules than the actual lipid, so-called ultrahydrophobes [ 47 ], into the lipid phase before PME. Previous studies have shown that Ostwald ripening was decelerated after the addition of ultrahydrophobes [ 37 , 48 , 49 , 50 ]. In theory, due to the addition of the ultrahydrophobe, the osmotic pressure in the droplets rises and exceeds the Laplace pressure.…”
Section: Resultsmentioning
confidence: 99%
“…A different way to achieve small-sized nanoemulsions with higher long-term stability is to incorporate more hydrophobic molecules than the actual lipid, so-called ultrahydrophobes [ 47 ], into the lipid phase before PME. Previous studies have shown that Ostwald ripening was decelerated after the addition of ultrahydrophobes [ 37 , 48 , 49 , 50 ]. In theory, due to the addition of the ultrahydrophobe, the osmotic pressure in the droplets rises and exceeds the Laplace pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Strongly hydrophobic compounds can be incorporated into the oil phase of essential oil emulsions to inhibit Ostwald ripening [23,24]. Ester gum is widely used in the beverage industry as a weighting agent [1], but it may play a dual role in stabilizing beverage emulsions by also acting as a ripening inhibitor.…”
Section: Influence Of Ester Gum Addition On Ostwald Ripeningmentioning
confidence: 99%
“…However, we believe that our results are better explained by the Ostwald ripening mechanism. First, since limonene, the major component (94-96%, depending on biological origin) in orange oil, could be dissolved in water to 13.8 mg/L [29], orange oil is known to be relatively polar oil [13,24], which makes it highly susceptible to Ostwald ripening. Ostwald ripening tends to occur more rapidly when the droplet size is small, which is a possible reason why Ostwald ripening occurred rapidly in our study, unlike the previous finding [28] (droplets prepared in this study were approximately 10 times smaller than those reported in the previous study).…”
Section: Storage Time (Day)mentioning
confidence: 99%
“…Furthermore, NEs require a lower quantity of surfactants than MEs, reducing potential toxicological problems [17]. The use of surfactants and emulsifiers minimises or prevents the occurrence of Ostwald ripening, prevents coalescence, and improves the antimicrobial activity of EOs [18]. Emulsifiers are a subcategory of surfactants which prevent oil droplet aggregation, increasing colloidal stability.…”
Section: Introductionmentioning
confidence: 99%